2018
DOI: 10.22207/jpam.12.4.32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage on the Level of Aflatoxin M1 in Milk and Other Dairy Products Sold at Tripoli Province, Libya

Abstract: Milk and dairy products are one of the chief sources of nutrition for human beings particularly for infant and children. Aflatoxin M 1 (AFM 1) a hydroxylated metabolite of aflatoxin B 1 found in milk and milk products causes serious health issues for human beings. The objective of this study was to evaluate the effect of storage on the level of aflatoxin M 1 in milk and other dairy products sold at retail stores of Tripoli Province, Libya. Selected samples (Skimmed and cream milk, infant milk formula, butter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, the results of the study showed that AFMI increased with increasing storage on the shelf. Expired products had higher concentrations compared to newly manufactured products >60.18 ng•kg −1 [46]. The results from studies assessing the occurrence of AFM1 in infant formula consistently show that some sample contains AFM1 levels beyond the EU.…”
Section: Breastmilkmentioning
confidence: 77%
“…Interestingly, the results of the study showed that AFMI increased with increasing storage on the shelf. Expired products had higher concentrations compared to newly manufactured products >60.18 ng•kg −1 [46]. The results from studies assessing the occurrence of AFM1 in infant formula consistently show that some sample contains AFM1 levels beyond the EU.…”
Section: Breastmilkmentioning
confidence: 77%